Criminal Threats Against The Injection of Empty Vaccines into the Body Based on Law Number 6 Year 2018 About Health Quarantine - Rama Dona; Bernat Panjaitan; Nimrot Siahaan (International Journal Labs, 2022)
Background: Currently, Indonesia has been running for 2 years with the COVID-19 pandemic that has spread to various corners of the country in Indonesia. The symptoms caused by this virus vary, namely Influenza, shortness of breath, or similar infections such as SARS and MERS. Objective: This study aims to find out and analyze the impact of the Covid-19 Vaccine on the Human Body and know and analyze the criminal provisions for perpetrators of empty vaccinations that are put into the body. Methods: This research belongs to the normative type of research. So it can be known that vaccines are a form of medical intervention to strengthen people's immunity in the midst of a pandemic, besides that it can also be known that the perpetrator of an empty vaccine injection case can be submitted to the court to be able to account for his actions if his actions do not have an element of negligence or negligence. Results: Corona Virus Disease-19 (COVID-19) has a significant impact on all aspects of human life in the world, especially in Indonesia which has a very large area and a large population (around 267 million people) with various professions. Vaccination is the process of administering a vaccine into the body. Conslusion: Based on the explanation above, it can be concluded that vaccines are a form of medical intervention to strengthen people's immunity in the midst of a pandemic.